كتاب السؤالات في العقيدة و علم الكلام - السوفي, أبي عمرو عثمان بن خليفة (مؤسسة منارة الإيمان, 2021)
Keywords: Foi – Traité – 12e siècle

كتاب السؤالات في العقيدة و علم الكلام - السوفي, أبي عمرو عثمان بن خليفة (مؤسسة منارة الإيمان, 2021)
Keywords: Foi – Traité – 12e siècle

كتاب السؤالات في العقيدة و علم الكلام - السوفي, أبي عمرو عثمان بن خليفة (مؤسسة منارة الإيمان, 2021)
Keywords: Foi – Traité – 12e siècle

كتاب السؤالات في العقيدة و علم الكلام - السوفي, أبي عمرو عثمان بن خليفة (مؤسسة منارة الإيمان, 2021)
Keywords: Foi – Traité – 12e siècle

كتاب السؤالات في العقيدة و علم الكلام - السوفي, أبي عمرو عثمان بن خليفة (مؤسسة منارة الإيمان, 2021)
Keywords: Foi – Traité – 12e siècle

منهج أبي عمار في الموجز: الإلهيات أنموذجا - الصقرية, عزاء بنت عبدالله بن سلام (جامعة السلطان قابوس, 2014)
University: كلية التربية
Keywords: Foi – Traité – 12e siècle

تبغورين الملشوطي وآراؤه الكلامية من خلال كتابه أصول الدين - سالم, محمد (جامعة الزيتونة, 2008)
University: المعهد الأعلى لأصول الدين
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-

Uṣūl al-dīn: The Fundamentals of the Faith: Tibghūrīn b. ʿĪsā al-Malshūṭī - Nāmī, ʿAmr Khalīfa al-; Le Gassick, Trevor (Harrassowitz Verlag, 2020)
This study presents, in Arabic original and in a close English translation, one of the earliest statements of the fundamentals of the faith of the Ibadiyya movement of Islam. Although in continuous existence since the earliest decades following the death of the Prophet Muhammad, adherents to this belief system have generally not played major political or military roles in the history of the Arab world. Their faith has, as a consequence, received remarkably little attention from scholars both Muslim and Western. The work entitled Kitab Usul al-din is an important Ibadi theological treatise. Its author, Tibghurin b. Dawud b. 'Isa al-Malshuti, native of the Djabal Nafusa (Libya), lived in the second half of the fifth century (12th century BCE). This author enjoys a very high reputation among the Ibadi community of the Maghrib. Indeed, the Kitab Usul al-din has been the subject of many commentaries and glosses, and the main questions of Muslim theology are addressed. The book aims to highlight the foundations (usul) of religion from which, according to the author, the community has divided into rival "paths" and divergent sects. The order followed is that of the great questions of Muslim theology and, for the first ten questions, the five theses: tawhid, 'adl, wa'id and wa'id, manzila, amr and nahy. The Quran is the basis of Tibghurin's argument. There is no chapter where it is not quoted abundantly (in total 247 citations). The unity of Tibghurin's book is based on the fundamental principle of tawhid (divine oneness) from which all articles of faith flow and tanzih (dissimilarity of God and the creature), as well as on original fidelity to ijma'. The credo of Tibghurin offers, in continuity with that of his predecessors, through a structured and balanced treaty, a global view of Ibadi theology of his time, on the basis of solid scriptural and rational argumentation.
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-

كتاب الأدلة والبيان المنسوب إلى الشيخ تبغورين الملشوطي: دراسة نقدية حول المؤلف والعنوان - فخار, جابر بن سليمان (المجلة الجزائرية للمخطوطات, 2023)
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-

منهج وآراء أبي عمار عبد الكافي الوارجلاني الاباضي (ت 570 ه) في رده على غير الإسلاميين من خلال كتابه الموجز - دراسة تحليلية - اولاد علي, محمد (جامعة الجزائر 1, 2023)
Keywords: Foi – Traité – 12e siècle

آراء الخوارج الكلامية: الموجز لأبي عمار عبد الكافي الأباضي - عبد الكافي, أبو عمّار (موفم للنشر, 2013)
Keywords: Foi – Traité – 12e siècle

الآراء الكلامية لأبي یعقوب الوارجلاني رسالة ماجستير في اصول الدين - خبزي, دليلة (مكتبة مسقط, 2009)
Keywords: Foi – Traité – 12e siècle

Uṣūl al-Dīn (The Fundamentals of the Faith). By Tibghūrīn b. īsā al-Malshūṭī. Edited by 'Amr Khalifa Ennami and translated into English by Trevor Le Gassick - Gaiser, Adam R. (Journal of the American Oriental Society, 2022)
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-; Recension

كتاب الدليل و البرهان لابي يعقوب يوسف ابراهيم الواجلاني (ت570هـ) دراسة و تحقيقا - كسكاس, عاشور يوسف (الجامعة الأمريكية العالمية, 2016)
Don de l'auteur
Keywords: Foi – Traité – 12e siècle

الآراء الكلامية للإمام أبي یعقوب الوارجلاني رحمه الله تعالى - خبزي, دليلة (جامعة الجزائر, 2002)
Keywords: Foi – Traité – 12e siècle

كتاب أصول الدين - الملشوطي, تبغورين بن داوود بن عيسى (2001)
Keywords: Foi – Traité – 12e siècle

Kuzey Afrika İbâzî Akidesi: Cenâvünî Örneği - Kılavuz, Ulvi Murat (Uludağ Üniversitesi İlahiyat Fakültesi Dergisi, 2015)
The Ibāḍī Creed of Maghrib: The Case of al-Janāwunī Abstract North Africa (Maghrib) had been very important for Ibāḍiyya since its formative period as the Ibāḍī creed shaped the theological identity of huge Berber-origin masses and the region has hosted their political structures that reached statehood. Thanks to the Khārijī/Ibāḍī principle of equality of all Muslims regardless of ethnic origins and the confidence that this principle provided to non-Arab elements, Berber tribes of Libya that Abū Zakariyyāʾ al-Janāwunī belonged to had been the earliest communities who accepted Islam in the region. Even though it has experienced minor evolution depending on sociopolitical conditions of the time and the region, the Ibāḍī creed of Maghrib came to this day by being in general congruence with the mainstream Ibāḍiyya. Al-Janāwunī had been a bridge transmitting the thought/creed of his predecessor Ibāḍī imāms to the generations coming after him and played a very central role in defining the boundaries of Maghrib Ibāḍī identity.
Keywords: Foi – Traité – 12e siècle

آراء الخوارج الكلامية: الموجز لأبي عمار عبد الكافي الأباضي - عبد الكافي, أبو عمّار (موفم للنشر, 2013)
Keywords: Foi – Traité – 12e siècle

Kitāb al-Adilla wa’l-Bayān - Malshūṭī, Tibghūrīn b. ʿĪsà b. Dāwud al- (Ministry of Heritage and Culture, 2009)
Keywords: Foi – Traité – 12e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-

أصول الدين أو الأصول العشرة عند الاباضية - الملشوطي, تبغورين بن داوود بن عيسى (مكتبة الجيل الواعد, 2005)
Keywords: Foi – Traité – 12e siècle